PELATIHAN PEMBUATAN ES KRIM MANGROVE PADA KELOMPOK MITRA USAHA MINA SENTOSA PATUGURAN REJOSO PASURUAN - Bambang Sutikno; Sri hastari; Yufenti Oktavia (Bajang Institute, 2023)
The use of mangrove fruit as a basic ingredient for drinks has not been carried out optimally, especially for coastal communities which are rich in mangrove forests. Socialization and training activities related to beverage products from mangrove fruit which have high nutritional content need to be held. Socialization and training activities are packaged in the form of community service in Patuguran village, Rejoso sub-district, Pasuruan district. The training activities were carried out together with home industry (micro-enterprise) women who are members of the Mina Sentosa group, Tambakrejo hamlet, Patuguran village to make processed mangrove es krim with 3 flavors, namely chocolate flavor, strawberry flavor and melon flavor made from mangrove raw materials. The method used in training is lecture, practice and mentoring methods. Lecture method by providing basic theory in processing mangrove fruit into es krim, so that it has added value in terms of taste and nutrition. The practical method is training that emphasizes personal skills to be able to make frozen drinks in the form of es krim. Assistance is provided for business continuity in terms of marketing with the aim of creating self-sufficiency to seek sustainable profits. The output of this community service activity is to produce frozen beverage products in the form of es krim with three flavors as an innovative and nutritious product, so that they can increase the income of women who are members of the Mina Sentosa group.